2019
DOI: 10.1021/acs.orglett.9b04233
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Reaction Approaches to Isoquinolones from 2-Vinylbenzaldehydes and Anilines via Imine Formation–6π-Electrocyclization–Aerobic Oxidation Sequence

Abstract: Two distinctive transition-metal-promoted aerobic oxidation protocols have been developed for the synthesis of isoquinolones from 2-vinylbenzaldehydes and aniline derivatives. Thus, the one-pot tandem reaction sequence of imine formation, thermal 6π-electrocyclization, followed by either Cu­(OAc)2-mediated or Pd­(OAc)2-catalyzed aerobic oxidation protocol allowed the ready access to isoquinolone derivatives. The control experiments revealed that the 1,2-dihydroisoquinoline intermediates from the 6π-electrocycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Besides the distinctive C–H functionalization/annulation reaction feature, this approach provides rapid access to isoquinolones and pyridinones, which present as core structural scaffolds in many natural products and pharmaceuticals of biological interest (Figure ). Albeit with several well-investigated methods for the synthesis of isoquinolinones, such as the intramolecular aminocarbonylation annulation reaction, the 6π-electrocyclization reaction, Larock-type heteroannulation reaction, and the C–H functionalization/annulation reaction of benzamides with alkynes or allenes, using the easily accessible alkenes as privileged synthons in the C–H functionalization/annulation reaction is still a valuable protocol. Additionally, using air as the terminal oxidant is another advantage regarding environmental friendliness and operational simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the distinctive C–H functionalization/annulation reaction feature, this approach provides rapid access to isoquinolones and pyridinones, which present as core structural scaffolds in many natural products and pharmaceuticals of biological interest (Figure ). Albeit with several well-investigated methods for the synthesis of isoquinolinones, such as the intramolecular aminocarbonylation annulation reaction, the 6π-electrocyclization reaction, Larock-type heteroannulation reaction, and the C–H functionalization/annulation reaction of benzamides with alkynes or allenes, using the easily accessible alkenes as privileged synthons in the C–H functionalization/annulation reaction is still a valuable protocol. Additionally, using air as the terminal oxidant is another advantage regarding environmental friendliness and operational simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…The method mainly focuses on the synthesis of pyrido fused heterocycles. This 3-component reactions of o-halo aldehydes 214, alkynes 114 and tertbutylamine (112) under Pd/Cu catalyzed reaction conditions leads the formation of isoquinolines in good yields (Scheme 153). [154] In the year 2016, Zhu et al reported a protocol for the synthesis of isoquinolines 2 using Pd-catalyzed CÀ H functionalization of aromatic oximes 92.…”
Section: Pd-catalyzed Isoquinoline Synthesismentioning
confidence: 99%
“…The protocol is revealed to be proceeding via 6π‐electrocyclization of 1‐azatrienes resulting in 1,2‐dihydroisoquinoline intermediates, which on aerobic oxidation yields the product isoquinolone (Scheme 89). [112] …”
Section: Synthesis Of Isoquinoline Derivativesmentioning
confidence: 99%
“…However, the use of electrocyclic reactions for the synthesis of heterocyclic compounds involves serious challenges due to the limited synthetic availability of azapolyenes of the required structure. Whereas 1-azabuta-1,3-dienes are readily available from a condensation of unsaturated carbonyl compounds with primary amines [13][14][15], the methods for the synthesis of their isomers, 2-azabuta-1,3-dienes, which include the Mannich olefination of alkylidene glycinates [16], the Wittig reaction of N-(diphenylmethylidene)oxamate [17], the coupling of imines with activated acetylenes [18], and the aza-Wittig reaction of Nvinylphosphazenes [19][20][21][22][23] are more complicated and allow the introduction of only a limited set of substituents. In recent years, another convergent approach to azapolyenes 6 and 9 based on the ring opening of three-and five-membered heterocycles 1 and 2 under the action of transition metal carbenes 3 has been intensively developed (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%